Adapting the Primary Care Assessment Tool for sub-Saharan Africa: a validation study - Robert Mash; Kefilath Bello; Innocent K Besigye; Anna Galle (BJGP Open)
Background: The World Health Organization’s (WHO) measurement framework for primary health care includes the core functions of primary care: first-contact access, comprehensiveness, coordination, continuity, and person-centredness. The Primary Care Assessment Tool (PCAT), originally developed in the USA, was adapted for use by four African countries, and can measure the core functions of primary care. Aim: To face and content validate a PCAT for sub-Saharan Africa that measures the core functions of primary care. Design & setting: Nineteen countries within the Primary Care and Family Medicine (PRIMAFAMED) network for sub-Saharan Africa participated in a validation study. Method: Two stages included a PRIMAFAMED workshop to assess face validity and a Delphi study to reach consensus on content validity among an expert panel as well as key stakeholders. Results: Thirteen countries participated in the workshop and suggested rephrasing 39 items, deleting six and adding four new items. Nineteen countries participated in the Delphi study and all 20 panel members reached consensus (>70%) on including the items as written. Seven experts and stakeholders reviewed the PCAT and suggested rephrasing 23 items, deleting one and adding one. The final PCAT for sub-Saharan Africa (SSA-PCAT) consists of 85 items that measure affiliation with the primary care facility, first-contact access and utilisation, comprehensiveness, continuity, coordination, and person-centredness, as well as health, demographic and socioeconomic status. Conclusion: The SSA-PCAT will now be piloted in Benin, Uganda, and South Africa. Further psychometric evaluation will be possible followed by more widespread use by researchers, district managers, and policymakers in the region.